Potentially F2m+igraphic sequences - Chen, Gang; Yin, Jian-Hua (Utilitas Mathematica, 2011)
Gould et al. considered a variation of the classical Turán-type extremal problems as follows: for a given graph H, determine the smallest even integer σ(H,n) such that every n-term graphic sequence π = (d i,d2,⋯,dn) with σ(π) = d 1 + d2 +⋯ + dn > σ(H,n) has a realization G containing H as a subgraph. In this paper, we determine the values of σ(F2m+i,n) for m > 4, i ε -1,0 and sufficiently large n, where F2m+i is the fan graph on 2m + i vertices.